THERAPEUTIC EFFECTS OF Myrmecodia sp. ON THE MORPHOLOGY OF FALLOPIAN TUBE EPITHELIAL CELLS IN MICE WITHPELVIC INFLAMMATORY DISEASE - Karlina, Siti; Hujjatusnaini, Noor; Sa’adah, Ayatus (Universitas Medan Area, 2025)
Pelvic Inflammatory Disease (PID) is a serious reproductive health issue affecting women of reproductive age, with Candida albicans as a common causative agent. This infection can damage the fallopian tube mucosa, increasing the risks of infertility, ectopic pregnancy, and chronic pelvic pain. With rising antimicrobial resistance, alternative therapies are needed. Myrmecodia sp. (ant plant) is a promising herbal candidate, rich in bioactive compounds such as flavonoids, tannins, terpenoids, and saponins, known for their antimicrobial, anti-inflammatory, and antioxidant properties. This study investigates the therapeutic effects of Myrmecodia sp. extract on the fallopian tube mucosa of BALB/c mice infected with Candida albicans. Using a true experimental post-test design, 24 mice were infected for four days and treated with varying concentrations of Myrmecodia sp. extract for seven days. Data were analyzed using ANOVA for vaginal color changes and the Kruskal-Wallis test for irritation. The results revealed that Myrmecodia sp. extract significantly reduced inflammation (p < 0.001) and showed a trend toward reduced irritation (p = 0.077). In conclusion, Myrmecodia sp. is a potential herbal therapy for PID caused by Candida albicans, offering a safe and effective option to support tissue regeneration and reduce complications.